The Ego Defense Mechanism of the Doctor Character in the Short Story Lailatu Ghaba Anha al Qamar by Najib Kaylani - Vidya, Siska Mei (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This research examines the representation of ego defense mechanisms used by the doctor character in resolving the conflicts he faces. The study applies Sigmund Freud’s literary psychology approach to analyze the ego defense mechanisms of the doctor character in the short story Lailatul Ghaba ‘Anha al Qamar by Najib Kaylani. The data source of this research is the short story Lailatul Ghaba ‘Anha al Qamar by Najib Kaylani. The data collection technique was carried out by reading and taking notes on important data relevant to the research. The results of this study confirm that the doctor character employs two defense mechanisms: suppression and sublimation. Overall, this research concludes that the purpose of the defense mechanisms used by the doctor character is to reduce his own anxiety while continuing to carry out his duties as a doctor